THE EFFECT OF SUBSTITUTION OF ANIMAL PROTEIN CONCENTRATE BY COTTONSEED CAKE IN COMMON CARP Cyprinus Carpio L. DIETS - Mahmoud A. Mohammad (Mesopotamia Journal of Agriculture)
A total of 90 common carp Cypinus carpio L. were cultured in glass aquria with average of initial weight 31 ± 2 gm/fish had been distributed randomly over five experimental diets , with three replication for each diet . The fish fed for 58 days on experimental diet which contained different rates of cottonseed cake ; Zero % (control diet , diet 1) and four diets contained 4.43, 8.7, 14.1, 16.9% of cottonseed cake of the total diet (2 , 3 , 4 and 5) respectively instead of 25, 50, 75 and 100 % of animal protein concentrate. Statistical analysis of results showed a significant differences were recorded between control diet and fish were fed at diet 4 & 5 for growth rate, relative growth rate and specific growth rate , food conversion ratio; protein efficiency ratio , protein sediment as well as protein productive value criteria , whereas there were no significant differences (P < 0.05) with fish fed at diet 1 & 2 for above criteria . It will be concluded that a possibility of replacing 50 % of animal protein concentrate by cottonseed cake without impacting on studied characteristics.